Challenges of marketing management of commercial enterprises in the 21st century - Stojanović Miloš; Mladenović Milica; Božić-Miljković Ivana (Megatrend Revija, 2023)
In contemporary turbulent environment, which is subject to frequent changes due to the influence of internal and external factors, managers must be expert and informed, and they must also act quickly. If trends are not accepted and followed, there is no survival on the market, which is true in all branches of business, and especially in the trade sector. Marketing managers must constantly monitor what is happening on the market, what innovations can affect their business, what the competition is doing, as well as what customers expect from them in order to best satisfy their wishes and needs, and ensure their loyalty. Digital technologies must certainly be adopted as a basis for doing business since not only do they offer the possibility of selling products online, but they also allow managers to obtain important information on their customers. Data on where customers interact, which social networks they use, how they think, as well as what their wishes and habits are, can make the process of making important decisions much easier for marketing managers of trading companies. For the purpose of this paper, empirical research was conducted through a survey on a sample of 112 managers of trading companies in Serbia in the period October-November 2022. The purpose of the research in this paper is to analyze how digitalization has influenced the change in managing B2B marketing of trading companies. The importance of determining this influence is reflected in the possibility of giving recommendations to managers of trading companies that have not yet joined the digital transformation of business to do so since today customers are mostly present on the Internet, which will be even more noticeable in the future as newer generations mature.